ENHANCED ANTI INFLAMMATORY ACTIVITY OF PHYTO-STABILIZED SILVER NANOPARTICLES ON CARRAGEENAN INDUCED PAW EDEMA IN RATS - K.M.APARNA MANI,; C.VASANTHI,; DARLING CHELLATHAI DAVID, (International Journal of Pharma and Bio Sciences, 2015)
Phytostabilized silver nanoparticles are being widely studied for its various pharmacological properties. In the present study silver nanoparticles synthesized using Black pepper extract was evaluated for its acute toxicity and also for its anti inflammatory activity in carrageenan induced paw edema in rats. The anti inflammatory effect was also compared against the commercial silver nanoparticles. The phyto-stabilised silver nanoparticles did not show any signs of toxicity at 300mg/kg given by intraperitoneal route. In the carrageenan induced paw edema model, the phytostabilised silver nanoparticles at 50mg/kg showed significant inhibition of paw edema at 2,3 and 5 hrs with a maximum of 62.50 % inhibition at the end of 5 hrs, thus exhibiting enhanced activity when compared to the commercial silver nanoparticles due to the additional properties of the capping phytochemicals.